Confederacin Per-Boliviana - Romero Sachn, Lucero Elizabeth (2021)
This work demonstrating professional proficiency entitled "Peru-Bolivian Confederation" _x000D_ theoretically and pedagogically sustains a learning experience corresponding to the area of _x000D_ social sciences, aimed at adolescents in their 4th year of secondary school, and considers a _x000D_ topic of importance in the history of our country. The purpose of the Peru-Bolivian _x000D_ Confederation was to create a state that would unite both countries, Peru and Bolivia, in _x000D_ order to unite the commercial routes that once existed in pre-Hispanic times, but _x000D_ unfortunately it was broken with the arrival of the Viceroyalty of the Ro de Plata and the _x000D_ creation of the State of Bolivia. As we will see, it did not come into being easily, rather _x000D_ there were many difficulties in the establishment process. In the end it was created through _x000D_ bloodshed, since not everyone was in agreement. Finally, we will see that the struggle with _x000D_ the dissolution persisted, therefore, battles occurred which brought victory to the end of the _x000D_ Peruvian-Bolivian Confederation, leaving political instability and the beginning of a _x000D_ military anarchy.